Separate growth charts and cephalometric norms for children with Down syndrome - Kurpik, Joanna; Matthews-Brzozowski, Artur (Journal of Medical Science, 2018)
Different phenotypic features characterizing the body structure of children with Down’s syndrome, which include low growth, small head, short limbs, as well as the tendency to obesity and other systemic diseases or congenital malformations, prompted the WHO to develop separate standards including growth charts for children with this syndrome. Selected authors in their studies also compare orthodontic parameters, and more precisely cephalometric parameters, between children with Down’s syndrome and healthy individuals. They note a tendency to repeated deviations from the accepted norms, including the skeletal class, antero-posterior dimensions of the jaw, the length of the base of the skull, the cranial base angle, and ANB, SNA, SNB angle. It is related to the occurrence of specific features of the skull skeleton structure, typical for children with Down’s syndrome. The described tendency of changes in cephalometric parameters, in correlation with the already developed separate growth charts to assess the growth of children with Down’s syndrome, leads to considerations on the need to develop separate standards in the field of orthodontics, adequately defining the skeletal structure of the facial part of the skull of these children.